Analisis Kebijakan Peraturan Gubernur Kalimantan Utara Nomor 21 Tahun 2021 Tentang Pedoman Penggunaan Batik Khas Daerah di Provinsi Kalimantan Utara - Purnomo (Hunatech Vol. XXX, No. XXX, 2022)
A statutory regulation to regulate certain materials to solve problems that exist in society and everything to fix general problems and ensure security so that each citizen tries and can carry out their respective functions. Judging from its function, the law with a responsive character is aspirational. That is a legal product that contains materials that are generally in accordance with the aspirations or will of the community it serves so that this legal product can be seen as a crystallization and will of the community. This article will analyze the background and context of the issuance of the Regulation of the Governor of North Kalimantan No.21 of the Year concerning Guidelines for the Use of Typical Batik for the Province of North Kalimantan and outline the facts, whether the product of the legislation is aspirational or not.